2007 7th IEEE Conference on Nanotechnology (IEEE NANO) 2007
DOI: 10.1109/nano.2007.4601180
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the motion of molecular machines on surfaces by STM: The nanocar and beyond

Abstract: To build up true molecular machines and understand the mechanics of nanoscale motion and manipulation in molecular system, we have created and investigated a family of molecules based around the concept of the nanocar, which has the rolling wheels made of spherical fullerene or carborane molecules. Assisted by scanning tunneling microscopy (STM), we have successfully characterized and manipulated these molecules. In addition, we have observed the behavior of these systems when thermal energy is applied. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…Consequently, a few experimental studies of nanocars have been accomplished. Zhang et al 20 reported one of the most valuable experimental observations and examined the motion of a few types of surface rolling molecules, including the nanocar. They reported that the nanocar remains almost motionless on the flat gold surface at temperatures lower than 200 °C, and it starts to move on the surface at the temperature of 200 °C.…”
Section: Validation Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, a few experimental studies of nanocars have been accomplished. Zhang et al 20 reported one of the most valuable experimental observations and examined the motion of a few types of surface rolling molecules, including the nanocar. They reported that the nanocar remains almost motionless on the flat gold surface at temperatures lower than 200 °C, and it starts to move on the surface at the temperature of 200 °C.…”
Section: Validation Of the Resultsmentioning
confidence: 99%
“…A specially developed scanning tunneling microscopy (STM) machine imaged the whole race. 14,18 Shirai et al 19 and Zhang et al 20 conducted experimental tests on first-generation nanocars in UHV conditions to investigate the motion of nanocars on a gold substrate. Claytor et al 21 studied the motion of some p-carborane wheeled nanocars on a metallic substrate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have utilized a bottom-totop approach and electronic structure computations to design icosahedral borane and carborane molecular architectures by starting with single molecules as well as with dimeric units connected directly or through bridges [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Knowledge of the electronic, magnetic, optical, and other properties of such single and dimeric units illuminates the evaluation of the global properties of 1D, 2D, or 3D superclusters and nanostructures [17][18][19][20][21][22]. The use of light to modify properties of nanostructures is at the heart of current cutting-edge technology.…”
Section: Introductionmentioning
confidence: 99%